Performance of Activated Carbon Adsorption and Ultrafiltration Membrane Hybrid Process for Leachate Treatment - Farah Diena, Nurin Nisa; Mahmud, Mahmud; Riduan, Rony; Kurnain, Ahmad (TROPICAL WETLAND JOURNAL, 2018)
Leachate is wastewater that contains pollutants dominated by organic matter. Conventional leachate treatments have some disadvantages therefore alternative treatments are needed. One of that alternative treatments is ultrafiltration membrane and adsorption as pretreatment. The aims of this study are to analyze adsorption isotherm and kinetic model for UV254 (UV adsorbance at 254 nm wavelength) adsorption, the performance of powdered activated carbon (PAC) adsorption and ultrafiltration membrane hybrid process for UV254 of leachate removal, and the effect of pretreatment towards membrane fouling. The result of this study are Freundlich isotherm and pseudo second order kinetic model best fitted model for ultrafiltration membrane hybrid process condition for UV254 removal level are at pH 6; 120 minutes contact time; and 4 g/L PAC doses. Adsorption as pretreatment can reduce membrane ultrafiltration fouling.